Richness, Diversity, and Conservation Status of Bird Species in Maron Beach, Semarang, Indonesia - Erik Prasetyo; Retno Wulandari (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2020)
Birds are important species that play a role in maintaining ecosystem stability. The land-use functions by humans can cause decreasing diversity of bird species. The purpose of this study was to identify species richness, species diversity, and conservation status of birds in Maron Beach, Semarang. The research was conducted in January 2017 using the point count method by five points. Observations were made at 06.00 - 10.00 WIB with a duration of 15-30 minutes for each point. The results showed that there were 42 bird species from 20 families. The species richness index (R1) showed a 6.629 value which is classified as a high category. Diversity index (H ') showed 2,915 value which is classified as a medium category. Conservation status of bird species that were protected by PP No. 7 1999, there were 7 bird species. Protected bird conservation status by P 106 2018, there were 3 bird species. The conservation status by IUCN is classified into 2 categories, that were Near Threatened (NT) and Least Concern (LC). The conservation status of international trade according to CITES indicates that no species are included in the list, but most of the bird species are traded locally.